Capital project cost estimation methodologies. The colombian case study (2019)
A literature review using databases of the main Colombian universities was made in order to define the theoretical form of capital cost estimation in Colombia. Given a review of global popular methodologies, this article presents an approach to emergent countries, especially Colombia. Up to now, there has not been a general rule or best practice for such estimation; on the contrary, diverse difficulties to be solved exist in an environment where the effects are global and different local situations arise. Academic and pragmatic authors find diverse postures, which makes recommendable to investors or shareholders to permanently evaluate the results. Currently, available models as Capital Asset Pricing are still used and adjust various proposals to its original structure.